2019
DOI: 10.3389/fpsyg.2019.02396
|View full text |Cite
|
Sign up to set email alerts
|

Deliberate Practice and Proposed Limits on the Effects of Practice on the Acquisition of Expert Performance: Why the Original Definition Matters and Recommendations for Future Research

Abstract: Over 25 years ago Ericsson et al. (1993) published the results of their search for the most effective forms of training in music, a domain where knowledge of effective training has been accumulated over centuries. At music academies master teachers provide students individualized instruction and help them identify goals and methods for their practice sessions between meetings – this form of solitary practice was named deliberate practice, and its accumulated duration during development was found to distinguish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
210
0
19

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(235 citation statements)
references
References 86 publications
(203 reference statements)
6
210
0
19
Order By: Relevance
“…Future studies should verify these findings, with a detailed analysis of the underlying mechanism. Despite the debate on the effect of age and accumulated practice over time among experts in the field of talent development [20][21][22], in this study older female athletes were more successful at the 2018EC. While swimmers may not improve their performance simply by aging, the present study should encourage swimmers under the age of peak performance, who did not reach semi-finals or finals at international competitions, to focus on mental skills and motivation to continue the hard work of high-level training and competition.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Future studies should verify these findings, with a detailed analysis of the underlying mechanism. Despite the debate on the effect of age and accumulated practice over time among experts in the field of talent development [20][21][22], in this study older female athletes were more successful at the 2018EC. While swimmers may not improve their performance simply by aging, the present study should encourage swimmers under the age of peak performance, who did not reach semi-finals or finals at international competitions, to focus on mental skills and motivation to continue the hard work of high-level training and competition.…”
Section: Discussionmentioning
confidence: 58%
“…It is believed that a certain amount of practice, i.e., 10'000 hrs, within a given time span, i.e., 10 yrs, is required to achieve expert level. This theory is hardly discussed among experts in the field [20,21,[39][40][41][42][43] and talent development most probably involves multiple factors [44]. Still, the high technical demand and specifics of in-water locomotion [9,34] may favour volume based training approaches and accumulated practice over time to achieve elite performance [45].…”
Section: Entriesmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards the process of swimmers’ sporting development, the present research revealed a tendency to differences in the number of hours of structured practice between the groups. Although several studies have emphasized the relationship between the number of training hours of an athlete and the performance level ultimately reached [ 35 ], it should be underlined that this refers not to any practice but only to appropriate quality training (deliberate practice, [ 36 ]). Those who resigned prematurely from competitive swimming had more hours of practice; however, the first phase of development, called the sampling years [ 22 ] or exploration stage [ 11 ], was significantly shorter and the second phase, which focused on developing skills and competences (i.e., the commitment stage), was significantly longer.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of learning at school they had, on average completed only just over half of their schooling. Before eminence can be reached, or the extremely long periods of deliberate practice required can be achieved, many more years of engagement are necessary (Ericsson and Harwell, 2019). Similarly, the study participants were only at the beginning of the musical instrument lessons.…”
Section: Discussionmentioning
confidence: 99%